Tantangan Mediator Dalam Penyelesaian Sengketa Tanah Melalui Mediasi Di Kantor Pertanahan - Andi Hartawati; Alwi Jaya; A.Silfiana Sirajuddin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The resolution of land disputes through mediation at the Land Office signifies a critical intersection between administrative authority and restorative justice, yet its efficacy remains constrained by multifaceted behavioral, institutional, and structural impediments. Although the mediator serves as a vital facilitator in navigating complex land conflicts, the high incidence of failed mediations underscores a pervasive culture of litigation and a fundamental lack of compromise among disputing parties. Systemic limitations, particularly regarding human resource constraints, limited budgetary allocations, and the absence of binding enforcement power for mediated agreements, significantly undermine the potential of this mechanism as a definitive resolution endpoint. This research demonstrates that the current mediation framework functions primarily as a preliminary negotiation phase rather than an instrument for conclusive justice. Addressing these integrated challenges through adaptive policy frameworks and robust institutional support is imperative to transform the Land Office into an effective hub for sustainable and equitable agrarian conflict resolution in regional areas.